2006
DOI: 10.1103/physrevlett.96.055509
|View full text |Cite
|
Sign up to set email alerts
|

Fracture Surfaces as Multiscaling Graphs

Abstract: Fracture paths in quasi-two-dimensional (2D) media (e.g thin layers of materials, paper) are analyzed as self-affine graphs h(x) of height h as a function of length x. We show that these are multiscaling, in the sense that n th order moments of the height fluctuations across any distance ℓ scale with a characteristic exponent that depends nonlinearly on the order of the moment. Having demonstrated this, one rules out a widely held conjecture that fracture in 2D belongs to the universality class of directed pol… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
49
3

Year Published

2006
2006
2015
2015

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 52 publications
(57 citation statements)
references
References 22 publications
3
49
3
Order By: Relevance
“…In this range of δz values, it would be possible to rescale all the moments (h(z + δz) − h(z)) p 1/p by using several exponents ζ p (not shown here): The relevance of such a multiscaling description at length scales for which the geometry of a single grain has a predominant effect is however questionable. These results bring new insight to a recently debated question concerning crack lines resulting from the rupture of paper sheets that were found to exhibit multiscaling [23], at least at small scales, i.e. at length scales comparable with the length of the fibers of the paper.…”
Section: B Statistical Distribution Of the Fluctuations Of Heightmentioning
confidence: 96%
“…In this range of δz values, it would be possible to rescale all the moments (h(z + δz) − h(z)) p 1/p by using several exponents ζ p (not shown here): The relevance of such a multiscaling description at length scales for which the geometry of a single grain has a predominant effect is however questionable. These results bring new insight to a recently debated question concerning crack lines resulting from the rupture of paper sheets that were found to exhibit multiscaling [23], at least at small scales, i.e. at length scales comparable with the length of the fibers of the paper.…”
Section: B Statistical Distribution Of the Fluctuations Of Heightmentioning
confidence: 96%
“…II we show that the statistical properties of rupture lines cannot be fully characterized by the scaling invariance of Eq. (16). In that case, the more complex structure of the probability distribution function leads to multiscaling in contrast with monoscaling implied by Eq.…”
Section: Figmentioning
confidence: 75%
“…In a recent work [16] we have shown that the phenomenology is much richer and fracture lines are multiscaling. An example that provides us with information of sufficient accuracy to establish the multiscaling characteristics is rupture lines in paper.…”
Section: Multiscaling In 1+1 Dimensional Fracturementioning
confidence: 99%
See 1 more Smart Citation
“…To quantify the fluctuations in the crack morphology as a function of the sample thickness, we follow the multiscaling analysis commonly employed to study fracture fronts [27,[38][39][40] and compute the q moments of the correlation function,…”
Section: Crack Front Roughness and Avalanchesmentioning
confidence: 99%